Mekanisme Pengembalian Kerugian Keuangan Negara Pada Tindak Pidana Korupsi Dalam Perspektif Peraturan Perundang-undangan Di Indonesia - Agustin, Lidya; Lasmadi, Sahuri; Monita, Yulia (Faculty of Law, Universitas Jambi, 2024)
Corruption has become a serious problem for every country in the world, including Indonesia. In 2022, based on the corruption perception index created by Transparency International, Indonesia will be in 110th position out of 180 countries with a score of 34. Therefore, it is very important for a country to have an effective mechanism, especially in the mechanism for recovering state financial losses in acts of corruption. This research discusses the Mechanism of Returning State Financial Losses in Corruption Crimes from the Perspective of Legislation in Indonesia. The aim of this research is to understand the regulation of returning state losses from criminal acts of corruption in Indonesia based on statutory regulations. This research uses various approaches, including conceptual approaches, legislation, cases, and normative juridical research types. The focus is on the mechanism for returning state losses in accordance with statutory regulations, as well as challenges in handling criminal acts of corruption. The research results show that the application of restorative justice in corruption cases reduces the burden on the state budget because there is no need to process and maintain perpetrators of criminal acts of corruption who are detained or convicted. However, the findings also show that there is a discrepancy with Article 4 of Law no. 31/1999, which states that restitution of losses to the state or the state economy does not eliminate the punishment of perpetrators of criminal acts intended in Article 2 and Article 3. ABSTRAK Korupsi telah menjadi masalah serius bagi setiap negara di dunia tidak terkecuali Indonesia. Pada tahun 2022 berdasarkan indeks persepsi korupsi yang dibuat oleh Transparency International Indonesia di posisi ke 110 dari 180 negara dengan skor 34. Oleh karena itu sangat penting suatu negara memiliki mekanisme yang ekfektif terutama dalam mekanisme pengembalian kerugian keuangan negara dalam tindakan korupsi. Penelitian ini membahas Mekanisme Pengembalian Kerugian Keuangan Negara Pada Tindak Pidana Korupsi Dalam Perspektif Peraturan Perundang-Undangan Di Indonesia. Tujuan penelitian ini adalah memahami pengaturan pengembalian kerugian negara pada tindak pidana korupsi di Indonesia berdasarkan peraturan perundang-undangan. Penelitian ini menggunakan berbagai pendekatan, termasuk pendekatan konseptual, perundang-undangan, kasus, dan tipe penelitian yuridis normatif. Fokusnya adalah pada mekanisme pengembalian kerugian negara sesuai dengan peraturan perundang-undangan, serta tantangan dalam penanganan tindak pidana korupsi. Hasil penelitian menunjukkan bahwa penerapan restorative justice dalam kasus korupsi mengurangi beban anggaran negara karena tidak perlu memproses dan memelihara pelaku tindak pidana korupsi yang ditahan atau dipidana. Namun, temuan juga menunjukkan adanya ketidaksesuaian dengan Pasal 4 UU No. 31/1999, yang menyatakan bahwa Pengembalian kerugian negara atau perekonomian negara tidak menghapuskan dipidananya pelaku tindak pidana sebagaimana dimaksud dalam Pasal 2 dan Pasal 3.